Xiao-Yao-San protects against anti-tuberculosis drug-induced liver injury by regulating Grsf1 in the mitochondrial oxidative stress pathway - Bai, Zijun; Tao, Weiwei; Zhou, Yiqun; Cao, Yi; Yu, Shun; Shi, Zheng (Frontiers in Pharmacology, 2022)
Background: Xiao-Yao-San (XYS) is a traditional Chinese prescription that regulates gastrointestinal function, improves mental and psychological abnormalities, and enhances liver function. However, the underlying mechanism of XYS for relieving anti-tuberculosis (AT) drug-induced liver injury is not clear. Objective: The current study examined whether XYS alleviated the symptoms of AT drug-induced liver injury in mice via the mitochondrial oxidative stress pathway. Methods: BALB/c male mice were randomly divided into four groups of 12 animals, including a control group, a model group, a 0.32 g/kg XYS group, and a 0.64 g/kg XYS group. The effect of XYS on the degree of liver injury was observed using haematoxylin and eosin staining (HE) and oil red O staining of pathological sections, biochemical parameters, and reactive oxygen species (ROS) levels. The protein expression of mitochondrial synthesis-related proteins and ferroptosis-related proteins was examined using Western blotting. Results: XYS improved the pathological changes in liver tissue and reduced the level of oxidative stress in liver-injured mice. XYS increased the expression of mitochondrial synthesis-related proteins and reversed the expression of ferroptosis-related proteins. Knockdown of G-rich RNA sequence binding factor 1 (Grsf1) expression with Grsf1 shRNA blocked the protective effects of XYS in liver injury. Conclusion: Our findings suggest that XYS alleviates AT drug-induced liver injury by mediating Grsf1 in the mitochondrial oxidative stress pathway.